Research On The Development Status Of Youth Women's Football In ChongQing Of China - Wang, Shaojie; Jiang, Bo (Quality in Sport, 2024)
Youth women's football is the hope of the future development of Chinese women's football, and it is a reserve force that needs to be cultivated. This paper analyzes and discusses the development of youth women's football in Chongqing by using literature and logical analysis methods, explores the new development path of youth women's football in Chongqing, and realizes the value of football policy. It is concluded that the development path of youth women's soccer in Chongqing should be sorted out again, the path should be comprehensively thought about, and the development system of youth women's soccer in Chongqing should be jointly promoted, so as to build a good development system of youth women's soccer and provide a better path for the development of youth women's soccer in Chongqing. Based on this, it is proposed to strengthen the construction of teacher team and improve the overall quality of football teachers. At the student level, football classes are set up based on interest; Talent training level: Build a smooth talent training mechanism, grasp the relationship between student learning and training, talent training system endowed with comprehensiveness and foundation; At the competition level, multi-party cooperation and participation will effectively integrate the teaching and sports sides of football matches.